Identification of Resistance Cultivars of Cowpea [Vigna unguiculata (L.) Walp] to Flower Thrips (Megalurothrips sjostedti Trybom) among Benin Germplasm - Tossou, T.H. (University Of Ghana, 2019)
Cowpea [Vigna ungriculata (L.) Walp] is a leguminous plant and is one of the staple crops much cultivated in Benin and neighboring countries and in Africa as a whole. Cowpea production is hindered by many biotic and abiotic factors, with the flower bud Thrips, Megalurothrips sjostedti (Trybom) being the most damaging pest at flowering stage causing yield losses of 20 to 80%. Control of flower bud thrips in the field is difficult due to its cryptic behaviour. Thus, the combination of control measures in addition to the use of resistant lines is promising. However, there is insufficient data on Benin cowpea germplasm resistance to flower bud thrips. Therefore, this study was aimed at identifying resistant cultivars to thrips among Benin germplasm and provide lines for breeding programs for eventual improvement of cowpea to the flower bud thrips in Benin. In order to identify resistant lines, the most damaging local population of flower bud thrips was selected among existing diversity, and cowpea accessions from greenhouses and the field screened for the trials. Flower bud thrips were collected from seven locations where cowpea is produced within two agro-ecological zones in Benin. The varying populations were reared, characterized on Sewe and vita7 (susceptible and resistant checks, respectively), and used to infest genotypes in the greenhouse. In greenhouse, 48 accessions were evaluated using CRD with three replicates. A total number of 25-30 nymphs at the fifth larval stage (6-7 days after hatching) were placed on single experimental plants. Data from the thrips damage and yield parameters were subject to variance analysis. Results showed that there were significant differences among accessions in terms of thrips damage and cowpea yield. Fourteen accessions (IT07K-243-1-10 (1), Sèwé (2), Sanzibanili (2), Awlétchi (3), Awonlignikoun (3), Gléssissaffodo (3), IT83S-742-2 (3), IT86D-888 (3), Kpègnikoun (3), Kpodjiguèguè (3), Kumassi (3), Moussa (3), Nontché-Wagbèhami (3) and Tiligré (3) were identified to be resistant (showing damage scores of 1 to 3) among the 48 tested, while the rest of the accessions presented high thrips damage scores (5-9). In order to evaluate the effect of environment on thrips damages, the same accessions were planted in three different locations, where cowpea is produced in Benin. The accessions were planted in an Alpha lattice design with three replications. Susceptible check (Vita7) was used as spreader rows surrounding each replication. Data were collected on thrips damage, thrips population per genotype at weekly intervals for four weeks, based on the commonly used scoring scale (1-9). Thrips damage scores and grain yield were subjected to Additive Main effects and Multiplicative Interaction (AMMI) and Genotype plus Genotype by Environment (GGE) biplot analyses. Genotype and genotype by environment interactions effects were not significant. A significant (P<0.001) difference was found between the accessions for thrips damage, adults and larvae of flower bud thrips on cowpea. Four accessions (IT84S-2246-4, Mawougbadonou, IT07K318-33, and IT93K-452-1) were found to be the most resistant and stable lines across locations. Based on the suitable environment analysis, the high yielding and the most adapted genotypes were Tawa, IT93K-452-1 and Kpodjiguèguè, with yield values of 101.88 Kg/ha-1; 227.16 Kg/ha-1 and 186.35 Kg/ha-1, respectively. This study provided status of screened accessions of which somes are resistants and others are high yielding and stable across environments. These accessions are relevents for breeders and could be used to improve cowpea’s resistance to the flower bud thrips and hence improve productivity and incomes of farmers in Benin.
MPhil. Entomology
Keywords: Cowpea; Vigna unguiculata (L.) Walp; Megalurothrips sjostedti Trybom; Flower Thrip; Benin Germplasm